Polariton spin Hall effect in a Rashba–Dresselhaus regime at room temperature - Liang, Jie (2024)
Exciton–polaritons—light–matter quasiparticles with spin degrees of freedom and ultrafast dynamics—are a promising platform for spin-based applications. However, an ongoing challenge is the generation and manipulation of high-purity polariton spins over macroscopic distances at room temperature. Here, by creating synthetic spin–orbit coupling in perovskite microcavities with liquid crystal molecules, we demonstrate the polariton spin Hall effect in the Rashba–Dresselhaus regime at room temperature, where spin-polarized polaritons with a high chirality of 0.88 are permanently separated as they propagate over 45 μm. We further show that their spin transport behaviours can be effectively manipulated by external electrical voltages. Our work represents an important step to generate purer polariton spin currents, paving the way to spin-optoelectronic applications with polaritons, such as spin lasers, spin filters and spin logic gates.